2014
DOI: 10.1021/pr500806k
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Study of Pilocytic Astrocytoma Pediatric Brain Tumor Intracystic Fluid

Abstract: Liquid chromatography in coupling with high-resolution ESI-LTQ-Orbitrap mass spectrometry was applied for a proteomic study of pediatric pilocytic astrocytoma brain tumor intracystic fluid by an integrated top-down/bottom-up platform. Both of the proteomic strategies resulted complementary and support each other in contributing to a wide characterization of the protein and peptide content of the tumor fluid. Top-down approach allowed to identify several proteins and peptides involved in different biological ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…No protein elements distinguished lateral (EP1 and EP5) from median line PF-EPs. Although without statistical significance in discriminating tumor localization or tumor grade, the top-down proteomic analysis characterized in ependymoma tissue other proteins and peptides that were already highlighted in our previous studies on other pediatric cerebral tumors in posterior cranial fossa [19,23]. They include ubiquitin and its C-terminal Gly-Gly dipeptide truncated form (Ubiquitin des-GG) -marking the most aggressive medulloblastoma-other fragments of GFAP and vimentin proteins, the bioactive C-terminal fragments of alpha-1-antichymotrypsin and alpha-1antitrypsin, the C-terminal peptide 375-418 of the latter with reported immunomodulatory activity [24], which would require further investigation to understand the actual biological role in the context of brain tumors.…”
Section: Top-down Proteomic Analysismentioning
confidence: 90%
“…No protein elements distinguished lateral (EP1 and EP5) from median line PF-EPs. Although without statistical significance in discriminating tumor localization or tumor grade, the top-down proteomic analysis characterized in ependymoma tissue other proteins and peptides that were already highlighted in our previous studies on other pediatric cerebral tumors in posterior cranial fossa [19,23]. They include ubiquitin and its C-terminal Gly-Gly dipeptide truncated form (Ubiquitin des-GG) -marking the most aggressive medulloblastoma-other fragments of GFAP and vimentin proteins, the bioactive C-terminal fragments of alpha-1-antichymotrypsin and alpha-1antitrypsin, the C-terminal peptide 375-418 of the latter with reported immunomodulatory activity [24], which would require further investigation to understand the actual biological role in the context of brain tumors.…”
Section: Top-down Proteomic Analysismentioning
confidence: 90%
“…Retains hematopoietic activity. Translation initiation from Met-25 may act as a fail-safe mechanism to maintain normal hematopoiesis when production of full-length RUNX1 protein is inhibited by genetic mutations [45] N-terminal modifications APP Several N-terminal proteoforms Proteoforms are enriched in Aβ soluble aggregates, a hallmark of Alzheimer's disease [46] CST3 Three N-terminal truncations: desS-, des-SSP, and des-SSPG des-S and des-SSP proteoforms are enriched in patients with type 2 diabetes mellitus and chronic kidney disease, while des-SSPG has been found in intracystic fluid of pilocytic astrocytoma pediatric brain tumors [49,50] (continued on next page) p53 proteoforms, were reported to have oncogenic functions [37]. The expression patterns and localization of p53 proteoforms (canonical p53, Δ40p53, and Δ133p53) were analyzed in endometrial carcinoma (EC) cells and endometrial nontumor cells [38].…”
Section: Gata1mentioning
confidence: 99%
“…Cystatin C (CysC) is a cysteine proteinase inhibitor used as a proxy for kidney function. In a study of 500 human plasma samples from a control population, two CysC proteoforms were reported as consequence of N-terminal truncations, one missing the N-terminal serine (des-S) and another lacking three N-terminal residues (des-SSP) [48,49]. Quantitative mass spectrometry immunoassays of CysC proteoforms in a cohort of patients with chronic kidney disease (CKD) with or without type 2 diabetes mellitus, showed that the levels of des-S and des-SSP were greater in the diabetic CKD group and could be used as markers for CDK progression [50].…”
Section: On the Influence Of N-terminal Modificationsmentioning
confidence: 99%
“…The first method (M1) consists in a simple procedure previously applied by our group to other bodily fluids . In this procedure the resulting extract represents the acid‐soluble fraction of LAF, purified from abundant proteins and depleted from possible lipid residues.…”
Section: Resultsmentioning
confidence: 99%
“…The LAF sample A, underwent four alternative pretreatment procedures, namely methods M1, M2, M3, and M4, to set up the optimum protein extraction procedure, which was therefore applied also to LAF sample B. M1 was a simple and rapid procedure, already described in our previous papers . Briefly, the samples were thawed at room temperature, acidified with 0.1 % (v/v) TFA aqueous solution and 2x volumes of ACN were added to deplete the most abundant and interfering proteins.…”
Section: Methodsmentioning
confidence: 99%